The impact of motivational interviewing on adherence and symptom severity in adolescents and young adults with chronic illness: A systematic review. Issue 12 (December 2017) - Schaefer, Megan R.; Kavookjian, Jan
Highlights: MI interventions may potentially improve adherence in AYAs with chronic illness. Youth with chronic illness may experience symptom reduction following MI. MI interventions may potentially enhance quality of life in youth. Only 4/12 retained studies were RCTS; therefore, further research is warranted. Abstract: Objective: Given the negative consequences associated with non-adherence in adolescents and young adults (AYAs) with chronic illness, it is important to identify interventions to address this issue. Therefore, this review's primary objective is to evaluate the impact of motivational interviewing (MI) on adherence and symptom level/severity in AYAs with chronic illness using a modified Cochrane method. Method: Four databases (e.g., CINAHL, Medline, PsychINFO, and International Pharmaceutical Abstracts) were systematically reviewed. 121 articles were identified in the initial search. Article eligibility was assessed on two tiers using the inclusion criteria. Results: Twelve articles were retained for data extraction. Diabetes, asthma, and HIV were the most common chronic illness populations examined in the study. Eleven of the twelve articles provided support for either improved adherence, symptom reduction, or a combination of both after participants received MI. Quality of life was also enhanced in three studies. Conclusion: Because adherence and symptom levels were positively impacted, it appears that MI may be a promising intervention for AYAs with chronic illness in addressing non-adherence and potentially improving quality of life. Practice implications: Healthcare providers should consider implementing MI in their practice to establish rapport and potentially improve long-term health outcomes for AYAs with chronic illness.